Risk of physical health comorbidities in autistic adults: clinical nested cross-sectional study - Megan Hunt; Jack F. G. Underwood; Leon Hubbard; Jeremy Hall (BJPsych Open)
Background Physical health conditions are more common in individuals with autism. Some, like epilepsy, have considerable evidence supporting their increased prevalence, but many diseases lack literature to make strong conclusions.